Optimized lovastatin production by solid-state fermentation with aspergillus terreus wildtype strain - Cabral, Maria Eugenia (2010)
Statins can inhibit the de novo cholesterol biosynthesis at the ratelimiting step of HMG-CoA reductase catalysis. For this reason,statins are clinically used as effective drugs forhypercholesterolemia treatment. Objective. This work was aimed atoptimizing and simplifying medium composition and fermentationconditions at shake-flask scale. In a second stage, these results weresubsequently applied for the massive lovastatin production by SolidSubstrate Fermentation (SSF). Methodology. Aspergillus terreusMEC was cultured by submerged fermentation (SF) in lactose-yeastextract medium, in shake flasks at 250 rpm and 25ºC during 14 days.Optimization included different C- and N- sources and the decreaseof salts and trace elements concentration. Additionally, theinfluence of soy flour incorporation and the replacement of lactoseby milk whey powder were evaluated. Different solid supports(sugarcane bagasse, wheat straw, soy flour) for SSF were assayed.Extracted lovastatin was analyzed by RP-HPLC with a Diode ArrayDetector. Results and conclusions. A lovastatin production of 63mg/L could be reached with optimized liquid medium. Productionwas significantly increased, up to ~1000 mg/L, by SSF includingcheap and readily available substrates such as whey milk adsorbedon textured soy flour, highlighting the relevance of fermentationstrategies for secondary metabolite production.